Strengthening Institutional Governance through Strategic Planning: Insights from Indonesian State Islamic Higher Education - Hidayah, Jumatul; Hamengkubuwono, Hamengkubuwono; Warlizasusi, Jumira; Faturrochman, Irwan (International Journal of Education Research and Development, 2025)
Strategic planning is a critical instrument for enhancing governance in State Islamic Higher Education Institutions (PTKIN) in Indonesia. This study explores the structure, content, and role of strategic plans within PTKIN as tools to align institutional goals with national educational policies, including the Merdeka Belajar–Kampus Merdeka program and the Religious Moderation Roadmap. Utilizing qualitative document analysis, this research used SWOT and TOWS frameworks to formulate adaptive strategies that address internal strengths and weaknesses as well as external opportunities and threats. The instrument also joined with the synthesis of many successful cases of strategic planning reported and government perspectives in many studies. The findings indicate that while PTKIN have developed comprehensive strategic plans, challenges persist in their implementation, particularly regarding monitoring, stakeholder involvement, and integration of moderate Islamic values into operational activities. The study concludes that effective strategic planning, supported by participatory processes, outcome-based indicators, and financial diversification, is essential for PTKIN to achieve sustainable institutional development and contribute meaningfully to national and global educational goals.